2020
DOI: 10.1101/2020.09.24.312496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The energetics of social signaling during roost location in Spix’s disc-winged bats

Abstract: Long-term social aggregations are maintained by multiple mechanisms, including the use of acoustic signals, which may nonetheless entail significant energetic costs. To date, however, no studies have gauged whether there are significant energetic costs to social call production in bats, which heavily rely on acoustic communication for a diversity of social tasks. We measure energetic expenditure during acoustic signaling in Spix’s disc-winged bats (Thyroptera tricolor), a species that commonly uses contact cal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
1
1
Order By: Relevance
“…Therefore, the production of "screech" calls in this species, while strongly associated with foraging activities, is not considered to be exclusively associated with a feeding context (Clay et al, 2012). In contrast, the evidence collected in our study, together with results of previous studies (Chaverri et al, 2018(Chaverri et al, , 2021Chaverri & Gillam, 2016;Chaves-Ramírez et al, 2023;Montero & Gillam, 2015), shows that food-associated calls in T. tricolor are emitted exclusively in a feeding context, and that calls prompt social recruitment. Future studies are needed to confirm that T.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Therefore, the production of "screech" calls in this species, while strongly associated with foraging activities, is not considered to be exclusively associated with a feeding context (Clay et al, 2012). In contrast, the evidence collected in our study, together with results of previous studies (Chaverri et al, 2018(Chaverri et al, , 2021Chaverri & Gillam, 2016;Chaves-Ramírez et al, 2023;Montero & Gillam, 2015), shows that food-associated calls in T. tricolor are emitted exclusively in a feeding context, and that calls prompt social recruitment. Future studies are needed to confirm that T.…”
Section: Discussioncontrasting
confidence: 84%
“…This type of call has not been previously described in disc-winged bats (Chaverri et al, 2018(Chaverri et al, , 2021Chaverri & Gillam, 2016;Montero & Gillam, 2015), and is markedly different from calls emitted by this species in situations of distress (Chaves-Ramírez et al, 2023). We also observed that vocalizations prompted two responses in receivers which are typically associated with food-calling (Clay et al, 2012), namely increasing feeding-related behaviors and social recruitment.…”
Section: Discussionsupporting
confidence: 41%
“…Age is also associated with RHP, since adults typically dominate over juveniles or subadults (Holand et al, 2004; Lu et al, 2013; Roden et al, 2005). Therefore, in our study we predict that dominance over positions within the roost will be primarily assigned to females, which are larger than males (Chaverri et al, 2021), and adults. Since we have not assessed the costs and benefits of different positions within the roost, we cannot accurately predict which position will be dominated by individuals with potentially greater RHP.…”
Section: Introductionmentioning
confidence: 86%